2018
DOI: 10.21873/invivo.11320
|View full text |Cite
|
Sign up to set email alerts
|

Human Emotions on the Onset of Cardiovascular and Small Vessel Related Diseases

Abstract: Abstract. Background Emotions and coronary heart disease. Coronary heart disease is a significant public health issue, due to its high prevalence and mortality rate (1). A number of clinical and experimental studies indicate that strong emotions, especially negative emotions, such as hostility, anger, depression and anxiety, precipitate coronary heart disease (2, 3). On the one hand, coronary heart disease patients have difficulty in coping with stress and depression and experience negative emotions, like ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 122 publications
1
12
0
Order By: Relevance
“…Recently, a study from the Add Health database performed path analysis linking adverse childhood experiences with later CVE risk but did not study negative emotions (Doom et al, 2017). Previous studies have also shown that improving emotional intelligence may reverse cardiac risk (Vlachakis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study from the Add Health database performed path analysis linking adverse childhood experiences with later CVE risk but did not study negative emotions (Doom et al, 2017). Previous studies have also shown that improving emotional intelligence may reverse cardiac risk (Vlachakis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these factors, many authors refer to the evidence of professional stress as a no less important factor and others identifies stress as being almost always present in the manifestations of cardiovascular disease, and emotional stress [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…The structural analysis of the TBK1 protein has been performed using the available human crystal structures (PDB 5W5V and 6NT9) of the TBK1 and it co-crystalized ligands with the MOE software (52). All the extracted conserved motifs from the previous steps, they have been identified and marked in the studied crystal structures (Figure 2 and 4).…”
Section: Structural Analysismentioning
confidence: 99%